2008
DOI: 10.1371/journal.pone.0002962
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological, Genetic and Gene Expression Features of a Novel Rodent Model of the Cardio-Metabolic Syndrome

Abstract: BackgroundComplex etiology and pathogenesis of pathophysiological components of the cardio-metabolic syndrome have been demonstrated in humans and animal models.Methodology/Principal FindingsWe have generated extensive physiological, genetic and genome-wide gene expression profiles in a congenic strain of the spontaneously diabetic Goto-Kakizaki (GK) rat containing a large region (110 cM, 170 Mb) of rat chromosome 1 (RNO1), which covers diabetes and obesity quantitative trait loci (QTL), introgressed onto the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…A chromosome 1 congenic with cardio-metabolic syndrome was constructed from BN and diabetic GotoKakizaki (GK) rats, but the donor region is proximal to the ZUC.BN-Chr1 congenic (23). Sex differences in UAE have been investigated in a congenic where SHR rats provide the donor chromosome 6 on the MWF rat background (19).…”
Section: Discussionmentioning
confidence: 99%
“…A chromosome 1 congenic with cardio-metabolic syndrome was constructed from BN and diabetic GotoKakizaki (GK) rats, but the donor region is proximal to the ZUC.BN-Chr1 congenic (23). Sex differences in UAE have been investigated in a congenic where SHR rats provide the donor chromosome 6 on the MWF rat background (19).…”
Section: Discussionmentioning
confidence: 99%
“…A colony of GK/Ox rats bred at Biomedical Service Unit, University of Oxford, since 1995 from a GK/Par stock and BN rats obtained from a commercial supplier (Charles River Laboratories, Margate, UK) were used to produce a series of 20 BN.GK and GK.BN congenic strains using a genetic marker-assisted breeding strategy (Wallis et al 2008). BN.GK congenics were designed to contain GK single genomic blocks introgressed onto the genetic background of the BN strain, whereas the reciprocal GK.BN congenics contained BN genomic blocks transferred onto a GK genetic background (Figure 1, Supplemental Material, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…This process resulted in the isolation of the GK strain enriched for naturally occurring Wistar polymorphisms that contribute to diabetes and associated phenotypes, which we previously mapped by QTL analysis of pathophysiological phenotypes in F2 crosses between GK rats and Brown–Norway (BN) controls (Gauguier et al 1996; Argoud et al 2006). Further physiological phenotyping and multitissue transcriptome profiling in a congenic strain designed to contain a large (∼100 Mb) QTL-rich region of the GK rat in a BN background validated QTL effects and suggested that congenics can be efficiently used to dissect out cis - and trans -mediated regulation of gene transcription (Wallis et al 2008). …”
mentioning
confidence: 99%
“…5). Recently, congenic and expression studies have shown that multiple loci within this region play a role in glycemic control (5,7,10,15,26,44). Furthermore, the homologous region in humans has been identified in several linkage studies (6,8,14,19,27,28,42,47), and three genes in this region have recently been identified in human genome wide association studies (GWAS) (Tcf7l2, HHEX and IDE) (34 -36, 38, 49).…”
Section: Discussionmentioning
confidence: 99%